Pertumbuhan Laba pada Perusahaan Pertambangan di Indonesia - Andriono Eko Yuniarto; Eka Noor Asmara; Herbowo Herbowo (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to examine the various determinants that affect profit growth. The determinant factors include: current ratio, debt to equity ratio, net profit margin, return on assets, and total assets turnover. The population of this study is all mining sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The sampling technique used purposive sampling method. The number of companies that meet the sampling criteria are 49. Data analysis was carried out through several analytical techniques, ranging from descriptive statistical tests, classical assumption tests and hypothesis testing. Hypothesis testing was performed using multiple linear regression analysis. The test results show that partially, the current ratio, debt to equity ratio, net profit margin, and return on assets have an effect on profit growth, while total asset turnover has no effect on profit growth. Simultaneously current ratio, debt to equity ratio, net profit margin, return on assets and total asset turnover affect profit growth. The value of the coefficient of determination is 64.4% which indicates that the determinant factors studied show an influence of 65.6% and the remaining 35.6% is influenced by other determinant factors. Based on the results of this study, further researchers can examine other determinants that are strongly suspected to also affect profit growth such as return on equity or other financial ratios. In addition, the results of this study can be used by companies to improve their financial performance by recognizing the influence of these various determinants.